Erratum - Passos, Felipe Dinau Leal; Guedes, Anderlúcia Corrêa; Melo, Ariela Gomes de; Varella, Renata de Queiroz; Rangel, Isabelle Carvalho; Carvalho, Ricardo de Souza; Ferry, Fernando Raphael de Almeida; Morais, Julia Sampaio de Souza; Passos, Carolina Varella Leal; Passos, Paula Varella Leal; et al. (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Erratum